Skateboard: Sudut Kaki dan Sudut Tumpuan Kaki pada Keseimbangan Trik Boardslide - Lestari, Endhah Tri; Edi Irwanto; Setyaningsih, Puji; Rubiono, Gatut (MAN Insan Cendekia Jambi, 2024)
The aim of this research is to obtain information on the relationship between foot angle and foot support angle on balance in skateboarding boardslide tricks. This research uses a descriptive with a quantitative approach. The assessment was carried out at the Gor Tawang Alun Skatepark arena with a sample size of 5 skateboard athletes. Angle data is collected by recording video, then the data is analyzed using the Kinovea application. To get balance results, the Modified Bass Test of Dynamic Balance test is used. The results of the research show that there is a relationship between the angle of the foot and the support of the foot on balance in the boardslide trick. The higher the balance value, the smaller the angle of the foot and foot support.